PMRI-based e-module development on sequences and series materials - Sari, Resti Auvita; Misdalina, Misdalina; Kesumawati, Nila (Desimal: Jurnal Matematika, 2021)
This research aims to produce e-module products based on Indonesian Realistic Mathematics Education (PMRI) on sequences and series materials that are valid, practical, and have potential effects. This research is a type of research and development using the ADDIE model, namely analyze, design, development, implementation, evaluation. The object of research is the quality of PMRI-based e-modules on sequence and series material. Before being tested, the e-module was validated by material experts and media experts. In addition, there is also a student response questionnaire regarding the developed e-module and test questions. The validity of the e-module has an average score of 92%, which is determined based on the results of the assessment of the e-module by experts consisting of 2 lecturers and 1 mathematics teacher. The practicality of the e-module has an average score of 87%, which is determined based on the student response questionnaire to the e-module. The potential effect aspect has an average score of 87% obtained based on student learning outcomes tests. The results of expert validation, student response questionnaires, and tests show that the e-module developed is very valid, very practical, and has a very high potential effect. Overall, PMRI-based e-modules on the sequences and series material for SMA class XI are suitable for use in learning.